The biology and ecology of juvenile pilotfish (Naucrates ductor) associated with Fish Aggregating Devices (FADs) in eastern Mediterranean waters - VASSILOPOULOU, V.; SIAPATIS, A.; CHRISTIDES, G.; BEKAS, P. (Mediterranean Marine Science, 2005)
The pilotfish (Naucrates ductor) is an epipelagic oceanic species, whose 0-group specimens tend to aggregate below flotsam, constituting a principal by-catch of the western Mediterranean FAD fishery. During a one-year survey sampling, monthly experimental hauls using surrounding nets were conducted at sites in south Peloponnesian waters, where FADs were moored; during the summer-early autumn months bongo tows were also carried out. 0-group pilotfish appeared beneath FADs from mid-summer till early winter and the total length of the collected specimens ranged between 120 and 330 mm. Pilotfish larvae, measuring 2.0- 3.9 mm, were found at FAD sites in mid-summer and in early autumn. The age of juvenile specimens, determined by counting daily increments on their sagittae, ranged between 50-141 increments (days) for males, and 51-131 increments (days) for females. The predicted asymptotic length was found to be 412.3mm TL for males and 435.2 mm TL for females. The onset of sexual maturity appeared to occur when specimens were a few months old. Stomach content analysis suggested that the diet of 0-group pilotfish associated to FADs in Greek waters depended mainly on decapod larvae, hyperiid amphipods, and alciopid polychaetes.